2012
DOI: 10.6064/2012/712605
|View full text |Cite
|
Sign up to set email alerts
|

Formins: Emerging Players in the Dynamic Plant Cell Cortex

Abstract: Formins (FH2 proteins) are an evolutionarily conserved family of eukaryotic proteins, sharing the common FH2 domain. While they have been, until recently, understood mainly as actin nucleators, formins are also engaged in various additional aspects of cytoskeletal organization and signaling, including, but not limited to, the crosstalk between the actin and microtubule networks. A surprising diversity of domain organizations has been discovered among the FH2 proteins, and specific domain setups have been found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 176 publications
0
7
0
Order By: Relevance
“…Plant formin homologs are quite different in structure and function [ 54 ]. Plant formins may play important roles in cell cortex organization, including cortical actin, microtubule cytoskeletons, and the attachment to the plasma membrane [ 55 ]. In this study, formin homolog EXTs (FH EXTs) were categorized as a third group of chimeric EXTs, as some of the formin homologs were found to have an N terminal signal peptide and contain a number of SP n repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Plant formin homologs are quite different in structure and function [ 54 ]. Plant formins may play important roles in cell cortex organization, including cortical actin, microtubule cytoskeletons, and the attachment to the plasma membrane [ 55 ]. In this study, formin homolog EXTs (FH EXTs) were categorized as a third group of chimeric EXTs, as some of the formin homologs were found to have an N terminal signal peptide and contain a number of SP n repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, FH2-mediated formin heterodimerization has been neither documented nor excluded yet in any organism, albeit dimerization via other domains was reported (see Cvrvčková, 2012). …”
Section: Membrane-associated Formins In Plants: the Known And The Posmentioning
confidence: 99%
“…Here studies in plants have led the way, with typical Class I formins predicted and later experimentally proven to be directly inserted into membranes, especially the plasmalemma (Banno and Chua, 2000; Cvrvčková, 2000; further experimental evidence reviewed below and in Cvrvčková, 2012 and van Gisbergen and Bezanilla, 2013). Also Class II formins often possess a domain related to metazoan phosphoinositide phosphatase PTEN, which may mediate their peripheral association with membranes (Cvrvčková et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…OsFH5 (also named RMD and BUI1) belongs to type II formin in plant, contains one PTEN (phosphatase and tensin homolog), one FH1 and one FH2 domain (Zhang et al, Yang et al), previous study showed that the mutants showed severe de ciency in most tissues of rice, such as, waved roots, dwarf lines, aberrant seeds shape, stronger sensitivity to gravity (Zhang et al, Huang et al, Song et al, 2019). PTEN domain of formins play important role in attaching with membrane, for instance, plasma membrane and chloroplast, mitochondrion, endoplasmic reticulum and so on (van Gisbergen and Bezanilla, Cvrckova, 2012, Cvrcková, 2013, while FH (formin homology domain)1 is used for binding pro lin/actin complex, FH2 is essential for nuclear activity (Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%